Picture-Based Insurance tools for improved risk management for the poor - CGIAR Platform for Big Data in Agriculture (2020)
Picture-based insurance was adopted by several insurance institutions and programs: HDFC ERGO General Insurance (India), Dvara E-Registry (India), Mahalanobis National Crop Forecast Center (India), ACRE Africa (Kenya), R4 Rural Resilience Initiative (Ethiopia), Centre for Agriculture and Bioscience International (India and Kenya).